Tantangan dan Strategi Inovatif Guru Pendidikan Agama Buddha dalam Mengembangkan Efektivitas Pedagogis dan Adaptasi Kontekstual: Systematic Literature Review - Partono Nyanasuryanadi; Eka Wulandari (Indo Publishing, 2026)
This study aims to systematically examine research findings related to teachers' pedagogical competence in facing the challenges and opportunities of learning in an era of educational change. The method used was a Systematic Literature Review (SLR) of a number of relevant scientific articles published in reputable journals. The results of the study indicate that teachers face internal challenges in the form of limited digital competence and literacy, as well as external challenges including infrastructure and curriculum demands. Various studies also reveal an increase in the adoption of learning innovations, such as blended learning, project-based learning, collaborative learning, and the use of digital technology. Technology integration has been shown to have a positive impact on pedagogical effectiveness, particularly in increasing student engagement and understanding, as well as teacher professionalism. Furthermore, teachers' ability to adapt learning strategies to the cultural context, local values, and student characteristics is a crucial factor in achieving meaningful and sustainable learning.